Factors influencing preceptorship in clinical learning for an undergraduate nursing programme in the North West Province of South Africa - Sesepo Maria Lethale; Lufuno Makhado; Magdalene Petronella Koen (Elsevier, 2019)
Background: The preceptorship model has been widely used as a method of choice for clinical learning in nursing education institutions worldwide, including South Africa. The aim of the study was to determine factors influencing preceptorship in clinical learning in an undergraduate nursing programme in nursing education institutions in the North West Province of South Africa. Methods: A cross sectional design was conducted among preceptors (n = 9), preceptees (n = 177) and unit managers (n = 38) using total population sampling technique. Data about factors influencing preceptorship were collected and analysed using descriptive statistics and the Statistical Package for Social Sciences (SPSS version 23). Results: The following factors influenced preceptorship positively: course expectations discussed at the beginning of placement, preceptors and unit managers with adequate knowledge to meet the preceptees' learning outcomes, hospital units were good clinical learning environments and good inter-professional relationships in the clinical areas. The factors that influenced preceptorship negatively included: the preceptors' perceived insufficient knowledge and skills to meet the preceptees' learning outcomes; and nurses in the units who did not support student supervision. Conclusion: Good interpersonal and inter-professional relationships between stakeholders are important to influence preceptorship positively as do preceptors and unit managers with adequate knowledge to meet preceptees' learning outcomes. Preceptorship could be enhanced by increasing the time spent in the clinical learning environment to meet expected preceptees' learning outcomes. Keywords: Preceptorship model, Clinical learning, Undergraduate nursing programme, Clinical learning environment